Pengembangan Bahasa Anak Usia Dini Melalui Metode Bercerita Di Lembaga Paud Meraje Gune - Azhari, Supian (Institut Agama Islam Negeri Ponorogo, 2021)
Early Childhood Language Development Through Storytelling Method at Meraje Gune PAUD Institution. This paper will explore the methods used in learning to develop early childhood language skills at the Meraje Gune PAUD Institution. The focus of this research will be on how to develop language at an early age by using the storytelling method in improving language skills at an early age. The study uses descriptive qualitative research where one of the studies that describes the findings or results in the field, observes and analyzes what is in the research. The results of this study indicate that, early childhood language learning using methods that can develop the potential of early childhood language. In fact, the influence of learning methods in developing children's language skills is by opening access to improve children's language skills, seeing from starting to speak, never feeling shy in asking questions, being active in various fields, namely storytelling, singing and being a leader in class.